Novel citric acid-functionalized brown algae with a high removal efficiency of crystal violet dye from colored wastewaters: insights into equilibrium, adsorption mechanism, and reusability. Issue 4 (21st March 2021) - Essekri, Abdelilah; Hsini, Abdelghani; Naciri, Yassine; Laabd, Mohamed; Ajmal, Zeeshan; El Ouardi, Mahmoud; Ait Addi, Abdelaziz; Albourine, Abdallah
Abstract: Synthetic dye waste is one of the world's key ecological concerns. The algal biomass has emerged as a promising alternative adsorbent for wastewater treatment. The present study deals with the functionalization of brown algae (BA) by citric acid in order to improve its adsorption ability for textile dye removal in aqueous solutions. The morphological texture (SEM and BET) and surface chemistry (FTIR, EDS-mapping, and PZC) of the novel functionalized brown algae (designated as BA-CA) were analyzed. The performance of BA-CA for crystal violet (CV) dye removal from wastewater was investigated. The isotherm and kinetic adsorption modeling indicate the good fit of Langmuir isotherm and pseudo-second-order models. Optimum monolayer uptake capacity was 279.14 mg/g for BA-CA, which was about two times higher than that of unmodified BA. The thermodynamic parameters clearly indicated that CV removal process was physiosorption, exothermic, and spontaneous in nature. The regeneration study showed excellent reusability of the BA-CA up to five cycles. Overall, the experimental findings lead us to conclude that the BA-CA can be used as an eco-friendly, cost-effective and easily regenerated adsorbent for the purification of textile effluents.